2017
DOI: 10.1093/pcp/pcx182
|View full text |Cite|
|
Sign up to set email alerts
|

Manipulation of Bryophyte Hosts by Pathogenic and Symbiotic Microbes

Abstract: The colonization of plant tissues by pathogenic and symbiotic microbes is associated with a strong and directed effort to reprogram host cells in order to permit, promote and sustain microbial growth. In response to colonization, hosts accommodate or sequester invading microbes by activating a set of complex regulatory programs that initiate symbioses or bolster defenses. Extensive research has elucidated a suite of molecular and physiological responses occurring in plant hosts and their microbial partners; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 106 publications
(165 reference statements)
0
35
0
Order By: Relevance
“…While the vast body of literature on how land plants deal with phytopathogens is focused primarily on angiosperms, research on gymnosperms and bryophytes is catching up [11-14] – yet, as highlighted by Upson et al [10], ferns and lycophytes have yet to follow suit. Further, at the present time, little is known about the interactions between streptophyte algae and their phytopathogens.…”
Section: Evolutionary Phytopathology: the Nuts-and-bolts Of Plant-micmentioning
confidence: 99%
“…While the vast body of literature on how land plants deal with phytopathogens is focused primarily on angiosperms, research on gymnosperms and bryophytes is catching up [11-14] – yet, as highlighted by Upson et al [10], ferns and lycophytes have yet to follow suit. Further, at the present time, little is known about the interactions between streptophyte algae and their phytopathogens.…”
Section: Evolutionary Phytopathology: the Nuts-and-bolts Of Plant-micmentioning
confidence: 99%
“…
Are effectors deployed during interactions with early diverging land plants?

Our current understanding of plant–microbe interactions is heavily skewed toward angiosperm models, with comparatively less known about how microbes interact with early diverging land plant lineages. This is especially true for plant–pathogen interactions, which are under-represented compared to interactions between early diverging land plants and symbiotic microbes [44,59]. Evidence for the direct action of effector molecules in early diverging lineages is lacking, yet several lines of evidence suggest that phytopathogens use effectors to manipulate these plants.

…”
Section: Unrelated Effector Molecules May Converge On Similar Networkmentioning
confidence: 99%
“…Whether this dynamic was established early during the coevolution of plants and microbes is unknown. Extensive evidence has demonstrated that early divergent land plants can accommodate arbuscules within their cells ( 7 , 17 ), whereas specialized pathogenic structures like haustoria have not been observed in these plants.…”
mentioning
confidence: 99%
“…This suggests that liverworts represent the earliest divergent land plant lineage, although this has yet to yield a consensus among the field ( 20 , 21 ). Many bryophytes are colonized by symbiotic microbes; however, intracellular endosymbiotic structures (arbuscules) have been observed only in liverworts and hornworts ( 7 , 17 , 19 ). Unfortunately, our understanding of plant–pathogen interactions in these plants is extremely limited.…”
mentioning
confidence: 99%